Effect of energetic neutrals on the kithul starch retrogradation; Potential utilization for improving mechanical and barrier properties of films. (1st January 2023) - Sudheesh, Cherakkathodi; Valiyapeediyekkal Sunooj, Kappat; Aaliya, Basheer; Navaf, Muhammed; Parambil Akhila, Plachikkattu; Ahmad Mir, Shabir; Sabu, Sarasan; Sasidharan, Abhilash; Pulissery Sudheer, Kundukulangara; Kumar Sinha, Suraj; Appukuttan Sajeevkumar, Vallayil; George, Johnsy
Highlights: Kithul starch showed significantly (p ≤ 0.05) higher amylose content after treatment. EAr atom treatment promoted the short and long-term retrogradation of starch. EArF-20 W exhibited the highest relative crystallinity (14.82 %) among the films. Films from retrograded EAr atoms treated starch has better tensile properties. Retrogradation of plasma treated starch improved the barrier functions of films. Abstract: The effect of energetic neutral argon (EAr) atoms on the short and long-term retrogradation was studied, and the retrograded starch was used to prepare bioplastic films for better mechanical and barrier properties. Kithul starch showed higher short and long-term retrogradation after treatment. The EAr atoms treatment increased amylose content and amylose leaching; it facilitated the short-term retrogradation. The more pronounced effect of long-term retrogradation in starch after treatment increased the enthalpy of retrogradation (ΔHR ), hardness, and syneresis and decreased the light transmittance and freeze–thaw stability. Bioplastic films made from retrograded starch after EAr atoms treatment exhibited significantly (p ≤ 0.05) higher relative crystallinity; it could be attributed to the higher starch retrogradation after cold plasma treatment. The films of retrograded EAr atoms treated starch showed higher mechanical strength and barrier properties. These results revealed that bioplastic films from retrograded EAr atoms treated starch could potentially substitute the single-use petroleum-based packaging films.